Vascular endothelial growth factor (VEGF) serum levelsof patients with Helicobacter pylori gastritis with cytotoxin-associated gene A positive (CagA+)status - Siregar, Wira Prihatin; Siregar, Gontar Alamsyah; Sungkar, Taufik (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Helicobacter pylori (H.pylori) is an agent that causes gastritis and the ulcer of gaster, which are ultimately caused gastric tumors. The prevalence is about 80 % average in developing country and 20-50 % in developed countries. One of the virulence factor iscytotoxin-associated gene A (CagA) that plays a role in the inflammation process,cell proliferation and metaplasia in gastric mucosa. Vascular endothelial growth factor (VEGF)is one of angiogenic factors that plays a role in the process of making new mucosal tissue after the inflammation by H.pylori. The escalation of VEGF expression levels contribute to the beginning of gastric carcinogenesis. The studywas aimed to analyze of VEGF serum levels between CagA(+) and CagA(-) in patients with H.pylori gastritis. Cross sectional study was conducted on 30 patients with H.pylori gastritis after conducted gastroscopy,biopsy and CLO test, which were continued with VEGF serum examination using ELISA test and perfomed PCR test to determinethe CagA status.The data was analyzed with SPSS 22 version andp value <0.05 was considered significant.The results of this study were18 men (60 %) and 12 women (46%) from 30 total subjects, with a median age average was 53.5 years old.Majority ethnic was Batak with 16 subjects (53.3%). Helicobacterpylori gastritis with CagA(+) was about 21 subjects (70%) and H.pylori gastritis with CagA(-) was about 9 subjects (30%). We found that median VEGF serum levels of patients with H.pylori gastritis with CagA(+)[480.3 pg/dL (115.5-2185.2)] significantly higher compared to thatwith CagA(-) [291.1 pg/dL (158.4-556.7)] (p<0.05).In conclusion, the VEGF serum levels ofpatients withH.pylori gastritis with CagA(+) is higher compared to that withCagA(-).